The Argonautica of Apollonius Rhodius, Book 4, 1-481 - Hulse, Peter (2015)
Before the publication of Professor Richard Hunter’s Cambridge Classics edition in August 2015, the last large-scale commentary on Apollonius Rhodius’ Argonautica Book 4 was that of Enrico Livrea in Italian in 1973, though mention should be made of the Budé volumes edited by Vian (1974–81). During this period the literary study of the poem has undergone a virtual revolution. The present thesis is an attempt to update and advance the work of the poem’s previous editors. It is intended as a prolegomenon to a commentary on the whole Book.